Methodology to improve the technique of the displacements in fencers - Carlos Alberto González-López; Carlos Alberto Lores-Real (Universidad de Guantánamo, 2018)
In the research, a methodology was set up to carry out exercises that contributed to improving the level of learning of the technique of the displacements in the fencers of the category 13-15 years of the Sports Initiation School "Pedro Díaz Coello" of Holguin, where deficiencies in the technique were detected in the displacements in the fencers of the aforementioned category and as a proposed objective was to contribute to improve the technique of the displacements in the fencers. Taking into account the foundations of fencing, its teaching, and its influence on physical development, the athletes under study, its characterization and the objectives in this category, were carried out in several stages with a duration of one year. As a result of the above, the technical level in the athletes of this category was increased.